Relationship between alexithymia and career decision -making self-efficacy among Tenth and Eleventh grade students in Muscat governorate - Hammoud, Mohammad Sheikh; Bakkar, Bakkar S.; Shendi, Yousef Abdulqader Abu; Al Rujaibi, Yousuf Saif (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2019)
The purpose of this study was to examine the relationship between alexithymia and career decision -making self-efficacy among Tenth and Eleventh grade students in Muscat governorate. To achieve this purpose, Alexithymia Scale (AS),and CDMSE Short Form were administered to a total sample of 556 students of Tenth and Eleventh grades ( (n = 278) males and (n = 278) females . Findings revealed that the level of alexithymia was less than the mean of items, while the level of CDMSE was more than the mean of items, as well as there was no significant correlational relationship between alexithymia and CDMSE. The findings also indicated that there were significant gender differences in alexithymia, while there were no significant gender differences in CDMSE. With regard to GPA, the findings revealed that there were no significant differences in alexithymia, while there were significant differences in CDMSE. Conclusion: It concludes that although there was no significant correlational relationship between alexithymia and career decision-making self-efficacy, alexithymia negatively affects individual’s decisions in life.